A successful pregnancy outcome after mitral valve replacement: a case report - Mishra, Vineet V.; Rane, Priyanka H.; Aggarwal, Rohina S.; Shah, Kunur N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Valvular heart disease can be acquired or congenital. Although the incidence of rheumatic heart disease is on the decline, the number of patients with congenital heart disease who survive into adulthood has grown substantially over the past 30 years. Therefore, a large number of patients with valvular heart disease will be of childbearing age. Here we presented a case of second gravida who was diagnosed with rheumatic heart disease and had undergone mitral valve prosthesis and tricuspid valve repair delivered a healthy live male baby weighing 2.250 kg.